The exploitation of emery on the island of Samos: Existing data and research perspectives - Stamatakis, Michael; Malegiannaki, Irini Athanasios (Bulletin of the Geological Society of Greece, 2018)
The possible exploitation of eastern Samos emery deposits during the antiquity is explored, taking into account the attested emery mining on the island, during the 19th and 20th c. A.D. Is it possible that Samos diasporitic emery had been used in a similar way with the diasporite and/or corundite emery of Naxos, the main and best known emery source in the Aegean archipelago? As a first step for the investigation of this question, existing geological and historical data on Samian emery are collated and then examined with reference to the Naxian mineral. As far as the mineralogical structure of the Samos emery is concerned, besides the existing data, XRD mineralogical analysis, XRF/ICP major and trace element analysis and SEM-EDS micro-analysis was conducted, in order to recognize specific features of the Samos diasporite deposit. Finally, the few known archaeological findings that may indicate a probable ancient exploitation of the Samos emery are presented, underlining the need of further geological and archaeological research in the Aegean Region and Western Anatolia, in order to draw wider conclusions.